Clinical platform for understanding the relationship between joint contact mechanics and articular cartilage changes after meniscal surgery. Issue 3 (13th February 2017) - Maher, Suzanne A.; Wang, Hongsheng; Koff, Matthew F.; Belkin, Nicole; Potter, Hollis G.; Rodeo, Scott A.
ABSTRACT: Injury to the meniscus of the knee has been implicated as a significant risk factor for the subsequent development of osteoarthritis, but the mechanisms of joint degeneration are unclear. Our objective was to develop a clinically applicable methodology to evaluate the relationship of joint contact mechanics at the time of surgery to biological changes of articular cartilage as a function of time following surgery. A series of pre‐, intra‐, and post‐operative protocols were developed which utilized electronic sensors for the direct measurement of contact mechanics, and advanced imaging to assess cartilage health. The tests were applied to a pilot cohort of young active patients undergoing meniscus allograft transplantation. Our study demonstrated significant variability across patients in terms of contact area and peak contact stress, both before and after transplantation. Nonetheless, the majority of patients exhibited decreased peak contact stress and increased contact area after graft implantation. MR scans at 3–6 months showed decreased T1ρ values in tibial articular cartilage, suggesting an increase in proteoglycan content or concomitant decrease in water content. Prolongation of T2 values was found primarily within the central, cartilage–cartilage contact region of the tibial plateau suggested disruption of the collagen network. Minimal differences were found in cartilage thickness over the short time frame of this preliminary study. With longer clinical follow‐up, our platform of clinical tests can be used to better understand the patient‐specific mechanical factors that are related to increased risk of OA after meniscus injury and surgery. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:600–611, 2017.